To examine the effect(s) of organisational change on knowledge workers post acquisition in an alcoholic beverage company in S.A. - Sebapalo, Boitumelo Itumeleng Antoinette (My University, 2021)
The aim of the study is to examine the effect(s) of organisational change on knowledge workers post acquisition in an alcoholic beverage company in South Africa and identify dynamics underlying organizational culture changes and their impact on knowledge workers. The research was focused on current and former employees of the organisation in South Africa who are considered knowledge workers at any level of management or speciality in the jobs they perform. In the viability analysis of the acquisition risk, cultural clash was identified as a concern by the leadership of the acquiring company. Previous work has looked at the successes and failures of Multi-National Company performance post an acquisition, but most have not addressed the impact of organisational change and organisational culture change on knowledge workers after a corporate acquisition. The research was conducted through the attainment of information from participants through an online survey. The research tested if the change was managed and if it reflected theoretical change management frameworks of Kurt Lewin’s and /or Josef Prosci’s ADKAR. The research questioned the relevance of some theoretical change management frameworks in transitional change. This implies looking at factors that warrant change (what are the gaps identified by those wanting the change or the rationale wanting for the change) and how the leaders effect the change. The research results indicated that there were changes in the organisation post the acquisition, the organisational change was managed and there was a change in organisational culture. The research suggested a larger sample or even, an equal number of participants of current and former employees to mitigate issues of bias in the study. Finally, the research also suggested that a designated team be responsible for managing change during the transition period (post the acquisition)
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science in Industrial Engineering